Principles of Biology Biology 211, 212, and 213 - Bartee, Lisa; Shriner, Walter; Creech, Catherine; Open Textbook Library (Minneapolis, MN Open Textbook Library, 2017)
The Principles of Biology sequence (BI 211, 212 and 213) introduces biology as a scientific discipline for students planning to major in biology and other science disciplines. Laboratories and classroom activities introduce techniques used to study biological processes and provide opportunities for students to develop their ability to conduct research.
Class Descriptions -- The Process of Science -- Chemistry for Biology -- Biological Molecules -- What is Life? -- Cell Structure and Function -- The Cell Membrane and Transport -- Cell Communication -- Enzyme-catalyzed reactions -- How cells obtain energy -- Photosynthesis -- Cell Division - Binary Fission and Mitosis -- BIOLOGY 212 - Genetics -- DNA and Chromosome Structure -- DNA Replication -- Mutations -- Protein Synthesis -- Gene Regulation -- Meiosis - Sexual Reproduction -- Patterns of Inheritance -- Genetics: Dog Coat Color -- Biotechnology -- BIOLOGY 213 - Ecology and Evolution -- Introduction to Evolution -- Evolution in Action -- Evolutionary Relationships -- Ecology and the Biosphere -- Population and Community Ecology -- Ecosystems -- Conservation Biology and Biodiversity
In English.
Description based on print resource
Keywords: Science -- Textbooks; Biology -- Textbooks